2021
DOI: 10.1002/mp.15377
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: Experimental determination of the effective point of measurement of the PTW‐31010 ionization chamber in proton and carbon ion beams

Abstract: Purpose:The accurate knowledge of the effective point of measurement (P eff ) is particularly important for measurements in proximity to high dose gradients such as in the distal fall-off of particle beams. For plane-parallel ionization chambers (ICs), P eff is well known and located at the center of the inner surface of the entrance window. For cylindrical ICs, P eff is shifted from the chamber's center toward the beam source. According to IAEA TRS-398, this shift can be calculated as 0.75⋅r cyl for light ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Palmans et al (2020) made a comprehensive analysis of experimental and Monte Carlo (MC) determined values of the EPOM for proton beams and confirmed the value of 0.75 x R for Farmer-type ICs. Barna et al (2022), however, found for a smaller cylindrical IC (Semiflex) in protons the EPOM to be greater than the value of 0.75 x R.…”
Section: Introductionmentioning
confidence: 70%
“…Palmans et al (2020) made a comprehensive analysis of experimental and Monte Carlo (MC) determined values of the EPOM for proton beams and confirmed the value of 0.75 x R for Farmer-type ICs. Barna et al (2022), however, found for a smaller cylindrical IC (Semiflex) in protons the EPOM to be greater than the value of 0.75 x R.…”
Section: Introductionmentioning
confidence: 70%
“…All the measurements were performed in water, irradiating perpendicularly to the detector surface. The overall uncertainty on the detector position was assessed to be 0.3 mm 40 …”
Section: Methodsmentioning
confidence: 99%
“…The overall uncertainty on the detector position was assessed to be 0.3 mm. 40 The Dos-μDos device was connected to the commercial electronic readout as depicted schematically in Figure 3b. On one side, the total charge generated in the SV of the dosimeter was acquired by a PTW UNIDOS electrometer using a triaxial cable once the irradiation field was completely delivered and, on the other side, the energy-deposition distribution in the SV of the microdosimeter was collected event by event by using a standard charge sensitive electronic chain.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Repeated measurements were carried out along the entire depth dose curve, resulting in a reproducibility of 0.55% expressed as one standard deviation. The general positioning uncertainty was assessed by taking into account the reproducibility, resolution of the water phantom scale, and positioning of both ionization chambers [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…In order to create the most physiological environment possible to enable reproducible in vitro studies, a novel water phantom-based setup was developed by our working group. The dosimetric characterization for both particle types has been carried out [ 10 ]. This setup allows comprehensive physics characterization of particle beams for pre-clinical research, in accordance with the report of a National Cancer Institute special panel [ 11 ] suggesting the linkage between high-quality biology data and high-quality physics data that go beyond the macroscopic parameter absorbed dose D in units of Gray.…”
Section: Introductionmentioning
confidence: 99%